Vegetation type modulates negative air ion generation in urban green spaces: the critical role of suburban forests in air quality enhancement - Xu, Yaowen; Jiao, Jiejie (Frontiers in Public Health, 2025)
Negative air ions (NAIs) are recognized as critical indicators of air quality and environmental well-being, with urban green spaces serving as vital sources of these beneficial ions. However, the spatiotemporal dynamics of NAIs across heterogeneous urban green infrastructure and their environmental determinants remain understudied. In this study, we examined the spatial and temporal distribution of negative air ions concentrations within various urban green spaces, specifically suburban forests, parks, roadside greenery, and community green spaces. A stratified sampling design was implemented across 240 georeferenced sites. At each site, NAIs concentrations were quantified using a three-phase measurement protocol:morning (8:00–9:30), midday (12:30–14:00) and evening (17:00–18:30). Field campaigns were conducted during the summer months (June to August) of 2024. Suburban forest areas showed significantly (p < 0.05) elevated NAIs levels compared to park, roadside greenery, and community green spaces, while roadside greenery displayed the lowest NAIs levels. We found that environmental factors, including relative humidity, temperature, air pressure, and particulate matter (PM10) concentration, significantly influence NAIs concentrations. Notably, relative humidity and temperature demonstrated a positive impact on NAIs levels, whereas air pressure and PM10 concentration showed a negative influence. These findings suggest that vegetation type, microclimatic conditions, and air quality have a crucial role in regulating NAIs generation and distribution. The study provides valuable insights for urban green space planning and management to enhance air quality and promote public health through optimized green infrastructure design.